ORAL ASSESSMENT IN TRIGGERING STUDENT HIGHER-ORDER THINKING SKILLS (HOTS) - Eka Mahendra (LPPM Universitas Negeri Jakarta, 2023)
Students' higher-order thinking skills (HOTS) due to the application of oral Assessment and Assessment are usually compared using experimental research in two separate groups. The experimental group consisted of 31 students, and the control group of 32 students was taken using a simple random sampling technique from a population of 315 students. Students' HOTS data were collected utilizing a test consisting of 5 items tested for validity, and the reliability coefficient was calculated. The collected data were then analyzed using a test (t-test), and the classical assumption test had previously been carried out. It turns out that the HOTS of students who are given an oral assessment is better than the HOTS of students who are given a regular assessment. Even though students are more afraid to face oral Assessment, they consider oral Assessment more beneficial than ordinary Assessment.